Erythrocyte membrane-coated NIR-triggered biomimetic nanovectors with programmed delivery for photodynamic therapy of cancer1. Issue 21 (7th June 2015) - Ding, Hui; Lv, Yanlin; Ni, Dezhi; Wang, Jie; Tian, Zhiyuan; Wei, Wei; Ma, Guanghui
<x xml:space="preserve">Abstract</x> A class of erythrocyte membrane-coated NIR-triggered nanovectors with programmed delivery is developed and its improved photodynamic therapy efficacy due to the synergistic effect of superior stealth ability, high efficacy of 1O2 generation and release, and the tumor-targeting and mitochondria-guiding is confirmed.